Analisis Deskriptif Untuk Memprediksi Kebutuhan Gula Mempergunakan Metode Manajemen Rantai Pasok - Muhammad Ramadhika Putra Tamtomo; Isnaeni Nurhidayah; Fika Anggraeni Lestari; Resad Setyadi (STMIK Budi Darma, 2022)
Granulated sugar is one of the production products in the agricultural sector and is an important staple in Indonesia. The basic needs of the Indonesian people, one of which is sugar, are a significant factor in increasing state revenues from the export side. However, the national demand for sugar continues to increase along with the increase in Indonesia's population. This has become a national problem in meeting the sugar needs of the Indonesian people. This study aims to analyze descriptively the sugar needs of the Indonesian people through researchers in the distribution channel of sugar in Indonesia. The data collection process used questionnaires and interviews to support descriptive analysis of supply chain management methods. The results showed that 70% of Indonesian people need sugar in their life. Recommendations from this study indicate that it is better to postpone the sugar export policy considering that the demand for sugar in Indonesia is very high.